Leader-Following Consensus of Multi-Agent Systems via Fully Distributed Event-Based Control - Geng, Zongsheng; Zhao, Dongdong; Zhou, Xingwen; Yan, Lei; Yan, Shi (Shanghai jiao tong da xue xue bao, 2024)
This paper aims to study the leader-following consensus of linear multi-agent systems on undirected graphs. Specifically, we construct an adaptive event-based protocol that can be implemented in a fully distributed way by using only local relative information. This protocol is also resource-friendly as it will be updated only when the agent violates the designed event-triggering function. A sufficient condition is proposed for the leader-following consensus of linear multi-agent systems based on the Lyapunov approach, and the Zeno-behavior is excluded. Finally, two numerical examples are provided to illustrate the effectiveness of the theoretical results.